Gaano katotoo ang laman ng mga diyaryo - Montiveros, Riza.; Vitug, Vet.; Aguilar, Mila D.; Papa, Joey C.; Institute for Filipino Cinema ([Quezon City] The Institute, 1989)
The local print media as seen by practitioners, movie stars and people on the street.
VHS
Host, Riza Montiveros; mga editor, Eric Caluen, Billy Belleza
Keywords: Newspapers; Mass communication; Journalism